Direct High-Precision Measurements of the 87Sr/86Sr Isotope Ratio in Natural Water without Chemical Separation Using Thermal Ionization Mass Spectrometry Equipped with 1012 Ω Resistors - Li, C.; Guo, J.; Chu, Z.; Feng, L.; Wang, Xuan-Ce (American Chemical Society, 2015)
Thermal ionization mass spectrometry (TIMS) allows excellent precision for determining Sr isotope ratios in natural water samples. Traditionally, a chemical separation procedure using cation exchange resin has been employed to obtain a high purity Sr fraction from natural water, which makes sample preparation time-consuming. In this study, we present a rapid and precise method for the direct determination of the Sr isotope ratio of natural water using TIMS equipped with amplifiers with two 1012 Ω resistors. To eliminate the 87Rb isobaric interference, Re ribbons are used as filaments, providing a significant advantage over W ribbons in the inhibition of Rb+ emission, based on systematically examining a series of NIST SRM987 standard doping with various amounts of Rb using Re and W ribbons. To validate the applicability of our method, twenty-two natural water samples, including different water types (rain, snow, river, lake and drinking water), that show a large range in Sr content variations (2.54–922.8 ppb), were collected and analyzed from North and South China. Analytical results show good precision (0.003–0.005%, 2 RSE) and the method was further validated by comparative analysis of the same water with and without chemical separation. The method is simple and rapid, eliminates sample preparation time, and prevents potential contamination during complicated sample-preparation procedures. Therefore, a high sample throughput inherent to the TIMS can be fully utilized.